The effect of ship bow shape on the hydrodynamic performance of ships - ميهوب غيث; ميشيل بربهان (Latakia University Journal -Engineering Sciences Series, 2023)
This study aims to highlight the role of the bow shape on the support ships by making a modification to the bow shape of the ship using MAXSURF Modeler and studying the resistances in calm waters using MAXSURF Resistance and the added resistances resulting from the oscillatory movements while sailing in addition to finding the capacity of the ship’s response to longitudinal and vertical movements using the program MAXSURF Motions